(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
This article discusses the meanings attributed to the educational process by teachers and young students at a Federal Institute of Education, Science, and Technology. The research was conducted using an ethnographic approach, including interviews with young students and focus groups with teachers. Professionals identify challenges such as the lack of dialogic spaces and alignment between institutional identity and teaching practice, which was consistent with the strong presence, in the narrative of students, of learning with a focus on the job market. These aspects showed the tension between neoliberal readings of the educational process and the institutional mission of guaranteeing rights and citizenship.